Advanced Physics / Materials and Mechanics: Volume I - Duncan Tom; John Murray (1987)
This book gives a complete up-to-date coverage of A level physics and its equivalents. Preface, Acknowledgements, Materials and Their Uses, Structure of Materials, Mechanical Properties, Electrical Properties, Thermal Properties, Optical Properties, Mechanics, Statics and Dynamics, Circular Motion and Gravitation, Mechanical Oscillations, Energy and Uses, Fluids at Rest, Fluids in Motion, Objective-Type Revision Questions, Appendices, Answers, Index.